Nation building, or Democracy by other means - Karimianpour, Hamid, 1968- (Algora Pub., 2011)
Despotism, fundamentalism, and the rise of terrorism have created a puzzling moral question in the twenty-first century: how far should America go to help press ahead political and cultural change in the world? The reader will discover that "while international pressure has often played a pivotal role in encouraging change," peaceful democratizations are historically not imposed from outside but are initiated and executed by leaders within the old system.